A composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials and a preparation method thereof

By using anion and cationic synergistic rust resistance technology and polymer emulsion to fill pores in alkali-excited gelling materials, the corrosion problem of steel bars of alkali-excited gelling materials under carbonization and chlorine salt erosion is solved, and its resistance to carbonization and chlorine resistance is significantly improved. The salt corrosion ability extends the durability of reinforced concrete.

CN116496026BActive Publication Date: 2025-02-11SOUTHEAST UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310366862.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-07
Publication Date
2025-02-11
Estimated Expiration
2043-04-07

AI Technical Summary

Technical Problem

Under the coupling effect of carbonization and chloride salt corrosion, alkali-activated gelling materials lead to corrosion of steel bars, affecting the durability of reinforced concrete. The prior art is difficult to improve its resistance to carbonization and chloride salt corrosion at the same time.

Method used

Using anion and cationic synergistic rust resistance technology, the composite material is formed by adding hydroxycarboxylic acid anions, polycarboxylic acid anions, cations and polymer emulsions to the alkali-excited gelling material, and the pores are filled with anion and cationic synergistic rust resistance and polymer emulsions. Improve the corrosion resistance of steel bars and the carbonization resistance of concrete.

Benefits of technology

It significantly improves the corrosion resistance and carbonization resistance of the steel bars in alkali-activated concrete, extends the durability of reinforced concrete, and at the same time, the raw materials used are environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116496026B_ABST
    Figure CN116496026B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite material for improving the steel bar protection and carbonization resistance of alkali-activated cementitious materials and a preparation method thereof. The composite material comprises (by mass percentage): 12-28% of hydroxycarboxylic acid anion component, 3-8% of polycarboxylic acid anion component, 8-17% of cationic component, 20-28% of polymer emulsion and 30-70% of water. The anions and cations with synergistic rust-inhibiting effects are used: the anions and the Fe 2+ , Fe 3+ Combine to form a complex; cations are directly adsorbed on the surface of the steel bar, creating more adsorption sites on the surface, which is conducive to the adsorption of anions on the surface of the steel bar to form a film, thereby improving the corrosion resistance of the steel bar. The polycarboxylic acid anion macromonomer is adsorbed on the surface of the steel bar to form a three-dimensional skeleton structure, and the anion and cation small monomers fill the unevenly adsorbed active sites and gaps, thereby improving the adsorption efficiency. The polymer emulsion enhances the anti-carbonation ability of alkali-activated concrete, ensures the durability of the concrete, and is green, environmentally friendly, and pollution-free.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite material for improving the reinforcement protection and carbonization resistance of an alkali-activated cementitious material and a preparation method thereof, and belongs to the technical field of reinforced concrete durability. Background Art

[0002] Concrete has the advantages of high strength, low porosity and low cost, which makes it the most widely used cement-based material in the world. However, cement production is one of the main sources of carbon emissions. Therefore, in order to reduce the energy consumption and related greenhouse gas emissions of cement clinker production, the construction industry has turned its attention to the reuse of waste materials from other industries. Alkali-activated cementitious materials are a type of cementitious materials produced by the reaction of siliceous and aluminous materials with volcanic ash activity or potential volcanic ash activity with alkaline activators. Since the synthesis of alkali-activated cementitious materials from fly ash or slag does not require high-temperature calcination, it can reduce carbon dioxide emissions in the cement production process. In general, alkali-activated cementitious materials have greater sustainable development potential than ordinary silicate cement, but due to the short research time, a complete industrial chain has not been formed, and relevant standards have not been formulated, so a lot of research is still needed.

[0003] Reinforced concrete is an economical, applicable and durable man-made composite material, but its durability has been a long-standing problem since its use. Among the many factors that affect the durability of concrete structures, cracking of concrete structures caused by steel bar corrosion is considered to be one of the main causes of durability failure of reinforced concrete structures. Carbonation and chloride attack are considered to be the two major factors leading to steel bar corrosion. Under alkali excitation system, Ca in raw materials 2+ The content is relatively low, so the Ca(OH)2 content in the product is very low and is easily carbonized. When alkali-activated concrete is carbonized at a relatively fast rate, it is easily invaded by chloride ions, which leads to steel corrosion. Therefore, steel corrosion in alkali-activated systems usually occurs under the coupling effect of carbonization and chloride salts. As an important research direction for the durability of reinforced concrete, steel corrosion is also very important in alkali-activated systems. Therefore, it is necessary to study it to provide a basis for the application of alkali-activated cementitious materials.

[0004] CN109437811 A discloses a method for enhancing the carbonation resistance of alkali-activated concrete. When preparing alkali-activated concrete, a certain amount of ordinary Portland cement is added to cause a hydration reaction to occur, thereby generating a large amount of Ca(OH)2, thereby improving the carbonation resistance of alkali-activated concrete. CN102531438 A discloses an alkali-activated slag mortar. By improving the proportion of the components of the alkali-activated mortar, the carbonation resistance of the mortar is improved. CN113896452 ​​A discloses an admixture for improving the carbonation resistance of concrete, and its preparation method and application. By adding solid waste materials such as mineral powder, silica fume and metakaolin to concrete, and introducing admixtures such as expansion agents, water reducers and waterproofing agents, the porosity of concrete is reduced, thereby improving the carbonation resistance and durability of concrete. It can be seen that there have been many studies on improving the carbonation resistance of alkali-activated concrete, but there are few studies on improving the carbonation resistance and chloride salt corrosion resistance of alkali-activated concrete at the same time.

[0005] In ordinary concrete, the use of rust inhibitors is one of the effective methods to control steel corrosion. Compared with other anti-rust measures, rust inhibitors are relatively low in cost and easy to handle. Rust inhibitors have good rust-resistant properties in ordinary Portland cement. Different types of rust inhibitors have been widely studied and have many applications, but they are less used in alkali-activated systems. Therefore, it is necessary to study the use of rust inhibitors in alkali-activated concrete to improve the corrosion resistance of steel bars. Summary of the invention

[0006] Purpose of the invention: The first purpose of the present invention is to provide a composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials. The second purpose of the present invention is to provide a method for preparing the composite material.

[0007] Technical solution: The present invention discloses a composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials. The composite material comprises the following components (by mass percentage): 12-28% of hydroxycarboxylic acid anion component, 3-8% of polycarboxylic acid anion component, 8-17% of cationic component, 20-28% of polymer emulsion, and 30-70% of water, and the sum of the mass percentages of the various components is 100%.

[0008] Furthermore, the hydroxycarboxylic acid anion component is hydroxycarboxylic acid or hydroxycarboxylate.

[0009] Furthermore, the hydroxycarboxylic acid is one or more of citric acid, tartaric acid, malic acid and maleic acid.

[0010] Furthermore, the hydroxycarboxylate is one or more of citrate, tartrate, malate and maleate.

[0011] Furthermore, the polycarboxylate anion component is polycarboxylic acid or polycarboxylate.

[0012] Furthermore, the polycarboxylic acid is one or more of polyvinyl acid, polyacrylic acid, and polymethacrylic acid.

[0013] Furthermore, the polycarboxylate is one or more of polyvinyl chloride, polyacrylic acid salt and polymethacrylate.

[0014] Furthermore, the cationic component is an amino acid salt.

[0015] Furthermore, the amino acid salt is one or more of leucine chloride, glycine chloride, lysine chloride, arginine chloride, cysteine ​​chloride, leucine nitrate, glycine nitrate, lysine nitrate, arginine nitrate, and cysteine ​​nitrate.

[0016] Furthermore, the polymer emulsion is one or more of water-based epoxy resin emulsion, water-based acrylate emulsion, and water-based methyltriethoxysilane emulsion.

[0017] The method for preparing the composite material for improving the reinforcement protection and carbonization resistance of the alkali-activated cementitious material of the present invention comprises the following steps:

[0018] The polycarboxylic acid anion component and the cationic component are sequentially added into water, and mixed and stirred evenly; then the hydroxycarboxylic acid anion component is added, and the mixture is continued to be mixed and stirred evenly; finally, the polymer emulsion is added, and the mixture is mixed and stirred evenly to obtain the product.

[0019] Furthermore, the mixing and stirring time is 2-5 minutes.

[0020] Furthermore, the time for continuing to mix and stir evenly is 1-3 minutes.

[0021] Furthermore, the time for mixing and stirring evenly is 5-10 minutes.

[0022] Mechanism: The present invention adopts the synergistic effect of anions and cations to prevent rust: anions and Fe 2+ , Fe 3+ Combine to form a complex; on the one hand, the cations are directly adsorbed on the surface of the steel bar, and on the other hand, more adsorption sites are generated on the surface of the steel bar, which is conducive to the adsorption of anions on the surface of the steel bar to form a film, thereby greatly improving the corrosion resistance of the steel bar; the polycarboxylic acid anion macromonomer is adsorbed on the surface of the steel bar to form a three-dimensional skeleton structure, and the anion and cation small monomers further fill the uneven adsorption active sites and gaps, improve the adsorption efficiency, and enhance the corrosion resistance of the steel bar; the polymer emulsion is used to fill the pores inside the concrete, thereby improving the carbonation resistance of the alkali-activated concrete and ensuring the durability of the alkali-activated reinforced concrete.

[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0024] The invention effectively improves the corrosion resistance of steel bars in alkali-activated concrete, and at the same time significantly improves the carbonation resistance of alkali-activated concrete, thereby ensuring the durability of concrete. The raw materials used in the invention are green and environmentally friendly, and have no pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the EIS graph of the steel bar after being exposed to the alkaline-excited extraction solution containing chloride salt for 1 hour. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0027] Example 1 Preparation of composite material A for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials

[0028] The raw material composition includes hydroxycarboxylic acid anion component, polycarboxylic acid anion component, cationic component, polymer emulsion and water. The raw materials are as follows by mass percentage: 18% of hydroxycarboxylic acid anion component, 6% of polycarboxylic acid anion component, 12% of cationic component, 22% of polymer emulsion and 42% of water.

[0029] The hydroxycarboxylic acid anion components are as follows by mass percentage: 30% citric acid, 40% sodium citrate, 10% tartaric acid, and 20% sodium tartrate.

[0030] The polycarboxylate anion components are as follows by mass percentage: 30% poly(ethylene acid), 40% sodium poly(ethylene acid), 10% poly(ethylene acrylic acid), and 20% sodium polyacrylate.

[0031] The cationic components are as follows by mass percentage: 10% of leucine chloride, 20% of glycine chloride, 20% of lysine chloride, 30% of arginine chloride, and 20% of cysteine ​​chloride.

[0032] The polymer emulsion comprises, by mass percentage, 30% of water-based epoxy resin emulsion, 30% of water-based acrylate emulsion and 40% of water-based methyltriethoxysilane emulsion.

[0033] The preparation steps are:

[0034] (1) Polyethylene acid, sodium polyethylene acid, polyacrylic acid and sodium polyacrylate are sequentially added into water and mixed, which is recorded as A1;

[0035] (2) adding leucine chloride, glycine chloride, lysine chloride, arginine chloride and cysteine ​​chloride into water in sequence and mixing, which is recorded as A2;

[0036] (3) citric acid, sodium citrate, tartaric acid and sodium tartrate are sequentially added into water and mixed, which is recorded as A3;

[0037] (4) mixing an aqueous epoxy resin emulsion, an aqueous acrylate emulsion and an aqueous methyltriethoxysilane emulsion, and recording the mixture as A4;

[0038] (5) A1 and A2 were added to water in sequence, and the mixture was stirred for 3 minutes. A3 was then added, and the mixture was stirred for 2 minutes until uniformly mixed. Finally, A4 was added, and the mixture was stirred for 8 minutes to obtain a composite material A.

[0039] Example 2 Preparation of composite material B for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials

[0040] The raw material composition includes hydroxycarboxylic acid anion component, polycarboxylic acid anion component, cationic component, polymer emulsion and water, wherein the mass percentage is: 18% of hydroxycarboxylic acid anion component, 6% of polycarboxylic acid anion component, 12% of cationic component, 22% of polymer emulsion and 42% of water.

[0041] The hydroxycarboxylic acid anion components are as follows by mass percentage: 10% malic acid, 30% sodium malate, 20% maleic acid, and 40% sodium maleate.

[0042] The polycarboxylate anion components are as follows by mass percentage: 30% polymethyl vinyl acid and 70% sodium polymethyl vinyl salt.

[0043] The cationic components are as follows by mass percentage: 20% leucine nitrate, 20% glycine nitrate, 20% lysine nitrate, 20% arginine nitrate, and 20% cysteine ​​nitrate.

[0044] The polymer emulsion comprises, by mass percentage, 30% of water-based epoxy resin emulsion, 30% of water-based acrylate emulsion and 40% of water-based methyltriethoxysilane emulsion.

[0045] The preparation steps are:

[0046] (1) poly(methyl vinyl) acid and sodium poly(methyl vinyl) salt are sequentially added into water, which is recorded as B1;

[0047] (2) adding leucine nitrate, glycine nitrate, lysine nitrate, arginine nitrate and cysteine ​​nitrate to water in sequence, denoted as B2;

[0048] (3) 10% malic acid, 30% sodium malate, 20% maleic acid and 40% sodium maleate were added to water in sequence, recorded as B3;

[0049] (4) mixing water-based epoxy resin emulsion, water-based acrylate emulsion and water-based methyltriethoxysilane emulsion, and recording it as B4;

[0050] (5) Add B1 and B2 to water in sequence, mix and stir for 3 minutes. Then add B3, mix and stir for 2 minutes. Finally, add B4, mix and stir for 8 minutes to obtain composite material B.

[0051] Comparative Example 1 Preparation of Composite Material C for Improving Reinforcement and Carbonization Resistance of Alkali-activated Cementitious Material without Adding Polymer Emulsion

[0052] The raw material composition includes hydroxycarboxylic acid anion component, polycarboxylic acid anion component, cationic component and water. The raw materials are as follows by mass percentage: 18% of hydroxycarboxylic acid anion component, 6% of polycarboxylic acid anion component, 12% of cationic component and 64% of water.

[0053] The hydroxycarboxylic acid anion components are as follows by mass percentage: 30% citric acid, 40% sodium citrate, 10% tartaric acid, and 20% sodium tartrate.

[0054] The polycarboxylate anion components are as follows by mass percentage: 30% poly(ethylene acid), 40% sodium poly(ethylene acid), 10% poly(ethylene acrylic acid), and 20% sodium polyacrylate.

[0055] The cationic components are as follows by mass percentage: 10% of leucine chloride, 20% of glycine chloride, 20% of lysine chloride, 30% of arginine chloride, and 20% of cysteine ​​chloride.

[0056] The preparation steps are:

[0057] (1) Polyethylene acid, sodium polyethylene acid, polyacrylic acid and sodium polyacrylate are added into water in sequence, which is recorded as C1;

[0058] (2) Leucine chloride, glycine chloride, lysine chloride, arginine chloride and cysteine ​​chloride are added to water in sequence, denoted as C2.

[0059] (3) citric acid, sodium citrate, tartaric acid and sodium tartrate are added to water in sequence, recorded as C3;

[0060] (4) C1 and C2 were added to water in sequence, and the mixture was stirred for 3 minutes. C3 was then added, and the mixture was stirred for 2 minutes to obtain composite material C.

[0061] Comparative Example 2 Preparation of composite material D for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious material without polycarboxylate anion component

[0062] The raw material composition includes hydroxycarboxylic acid anion component, cationic component, polymer emulsion and water. The raw materials are as follows by mass percentage: 18% of hydroxycarboxylic acid anion component, 12% of cationic component, 22% of polymer emulsion and 48% of water.

[0063] The hydroxycarboxylic acid anion components are as follows by mass percentage: 30% citric acid, 40% sodium citrate, 10% tartaric acid, and 20% sodium tartrate.

[0064] The cationic components are as follows by mass percentage: 10% of leucine chloride, 20% of glycine chloride, 20% of lysine chloride, 30% of arginine chloride, and 20% of cysteine ​​chloride.

[0065] The polymer emulsion comprises, by mass percentage, 30% of water-based epoxy resin emulsion, 30% of water-based acrylate emulsion and 40% of water-based methyltriethoxysilane emulsion.

[0066] The preparation steps are:

[0067] (1) adding leucine chloride, glycine chloride, lysine chloride, arginine chloride and cysteine ​​chloride into water in sequence and mixing, which is recorded as D1;

[0068] (2) citric acid, sodium citrate, tartaric acid and sodium tartrate are sequentially added into water and mixed, which is recorded as D2;

[0069] (3) mixing water-based epoxy resin emulsion, water-based acrylate emulsion and water-based methyltriethoxysilane emulsion, and recording it as D3;

[0070] (4) D1 and D2 were added to water in sequence, and the mixture was stirred for 3 min. D3 was then added and stirred for 6 min to obtain composite material D.

[0071] Comparative Example 3 Preparation of Composite Material E for Improving Reinforcement and Carbonization Resistance of Alkali-Activated Cementitious Material without Hydroxycarboxylic Acid Anion Component

[0072] The raw material composition includes polycarboxylic acid anion component, cationic component, polymer emulsion and water, and the mass percentage is: polycarboxylic acid anion component 6%, cationic component 12%, polymer emulsion 22%, water 60%.

[0073] The polycarboxylate anion components are as follows by mass percentage: 30% polymethyl vinyl acid and 70% sodium polymethyl vinyl salt.

[0074] The cationic components are as follows by mass percentage: 20% leucine nitrate, 20% glycine nitrate, 20% lysine nitrate, 20% arginine nitrate, and 20% cysteine ​​nitrate.

[0075] The polymer emulsion comprises, by mass percentage, 30% of water-based epoxy resin emulsion, 30% of water-based acrylate emulsion and 40% of water-based methyltriethoxysilane emulsion.

[0076] The preparation steps are:

[0077] (1) poly(methyl vinyl) acid and sodium poly(methyl vinyl) salt are sequentially added into water, which is recorded as E1;

[0078] (2) adding leucine nitrate, glycine nitrate, lysine nitrate, arginine nitrate and cysteine ​​nitrate to water in sequence, recorded as E2;

[0079] (3) mixing water-based epoxy resin emulsion, water-based acrylate emulsion and water-based methyltriethoxysilane emulsion, denoted as E3;

[0080] (4) E1 and E2 were added to water in sequence, and the mixture was stirred for 3 minutes. Then E3 was added, and the mixture was stirred for 6 minutes to obtain composite material E.

[0081] Comparative Example 4 Preparation of a composite material F containing no cationic components for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials

[0082] The raw material composition includes hydroxycarboxylic acid anion component, polycarboxylic acid anion component, polymer emulsion and water, wherein the mass percentage is: 18% of hydroxycarboxylic acid anion component, 6% of polycarboxylic acid anion component, 22% of polymer emulsion and 54% of water.

[0083] The hydroxycarboxylic acid anion components are as follows by mass percentage: 10% malic acid, 30% sodium malate, 20% maleic acid, and 40% sodium maleate.

[0084] The polycarboxylate anion components are as follows by mass percentage: 30% polymethyl vinyl acid and 70% sodium polymethyl vinyl salt.

[0085] The polymer emulsion comprises, by mass percentage, 30% of water-based epoxy resin emulsion, 30% of water-based acrylate emulsion and 40% of water-based methyltriethoxysilane emulsion.

[0086] The preparation steps are:

[0087] (1) poly(methyl vinyl) acid and sodium poly(methyl vinyl) salt are sequentially added into water, which is recorded as F1;

[0088] (2) 10% malic acid, 30% sodium malate, 20% maleic acid and 40% sodium maleate were added to water in sequence, recorded as F2;

[0089] (3) mixing water-based epoxy resin emulsion, water-based acrylate emulsion and water-based methyltriethoxysilane emulsion, and recording it as F3;

[0090] (4) F1 and F2 were added to water in sequence, and the mixture was stirred for 3 minutes. Then F3 was added, and the mixture was stirred for 6 minutes to obtain composite material F.

[0091] Example 3 Performance Test

[0092] 1. Electrochemical impedance spectroscopy (EIS) test

[0093] (1) Sample preparation. Low carbon steel bars were processed into steel bar electrodes. The steel bar electrodes were ground with silicon carbide paper, then polished with diamond polishing agent, and finally rinsed with deionized water and ethanol. The prepared steel bar electrodes were placed in a corrosion tank.

[0094] (2) At room temperature (22° C.), 920 g of deionized water, 80 g of NaOH and 1000 g of fly ash were mixed, stirred in a closed container for 24 h, and filtered to obtain a filtrate.

[0095] (3) The composite material A obtained in Example 1 was added to the filtrate, and after the system was stabilized, an electrochemical test was performed.

[0096] (4) The mass concentration of composite material A is 3% of the simulated liquid. The concentration of chloride salt is 2M.

[0097] (5) Electrochemical testing was performed using a classic three-electrode system: a working electrode (steel electrode), a counter electrode (platinum electrode) and a reference electrode (saturated calomel electrode, SCE). The same experiment was performed on Example 2 and Comparative Examples 1-4.

[0098] The composite materials obtained in Examples 1-2 and Comparative Examples 1-4 were subjected to electrochemical impedance spectroscopy (EIS) tests. The results are as follows: Figure 1 Described by Figure 1 It can be seen that the capacitance arc radius of the steel bars in Examples 1 and 2 is significantly larger than that in Comparative Examples 1, 2, 3 and 4, indicating that in the alkali-activated extract, the synergistic rust inhibition effect of anions and cations is better than the rust inhibition effect of a single anion, and the anion and cation small monomers can effectively fill the gaps in the polycarboxylate anion macromonomers, increase the adsorption rate on the steel bar surface, and improve the rust inhibition efficiency.

[0099] 2. Carbonization depth test

[0100] (1) The composite material A prepared in Example 1 was added to concrete, wherein the concrete was a mixture of fly ash sand, stone and water, and the mass fraction of the composite material A was 4% of the fly ash, to obtain a concrete specimen A. The above process was repeated in Example 2 and Comparative Examples 1-4, respectively, to obtain corresponding concrete specimens.

[0101] (2) The carbonation depth test method shall be carried out in accordance with the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2009).

[0102] (3) In this test, a concrete carbonation test chamber was used to rapidly carbonize the concrete specimens obtained above. The side length of the concrete cube specimens was 50 mm and the test age was 28 days.

[0103] The carbonization depth test was performed on the composite materials obtained in Examples 1-2 and Comparative Examples 1-4. The results are shown in Table 1.

[0104] Table 1 Carbonation test results of alkali-activated concrete after exposure to carbonation conditions for 28 days

[0105]

[0106] As can be seen from Table 1, the carbonization depth of Comparative Example 1 in which no polymer emulsion is added is significantly greater, indicating that the polymer emulsion used can effectively improve the carbonation resistance of alkali-activated concrete.

Claims

1. A composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials, characterized in that: The composite material comprises the following components, calculated by mass percentage: 12-28% of a hydroxycarboxylic acid anion component, 3-8% of a polycarboxylic acid anion component, 8-17% of a cationic component, 20-28% of a polymer emulsion, and 30-70% of water, the sum of the mass percentages of the various components being 100%, the cationic component being an amino acid salt, and the polymer emulsion being one or more of an aqueous epoxy resin emulsion, an aqueous acrylate emulsion, and an aqueous methyltriethoxysilane emulsion.

2. The composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials according to claim 1, characterized in that: The hydroxycarboxylic acid anion component is a hydroxycarboxylic acid and / or a hydroxycarboxylate salt.

3. The composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials according to claim 2, characterized in that: The hydroxycarboxylic acid is one or more of citric acid, tartaric acid, malic acid, and maleic acid, and the hydroxycarboxylate is one or more of citrate, tartrate, malate, and maleate.

4. The composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials according to claim 1, characterized in that: The polycarboxylate anion component is a polycarboxylic acid and / or a polycarboxylate salt.

5. The composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials according to claim 4, characterized in that: The polycarboxylic acid is one or more of polyvinyl acid, polyacrylic acid and polymethacrylic acid, and the polycarboxylate is one or more of polyvinyl salt, polyacrylic acid salt and polymethacrylate.

6. The composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials according to claim 1, characterized in that: The amino acid salt is one or more of leucine chloride, glycine chloride, lysine chloride, arginine chloride, cysteine ​​chloride, leucine nitrate, glycine nitrate, lysine nitrate, arginine nitrate and cysteine ​​nitrate.

7. The method for preparing a composite material for improving the reinforcement protection and carbonization resistance of alkali-activated cementitious materials according to any one of claims 1 to 6, characterized in that: The following steps are involved: The polycarboxylic acid anion component and the cationic component are sequentially added into water and mixed and stirred evenly; then the hydroxycarboxylic acid anion component is added and continued to be mixed and stirred evenly; finally, the polymer emulsion is added and mixed and stirred evenly to obtain the product.

8. The preparation method according to claim 7, characterized in that: The time for mixing and stirring evenly is 2-5 min, the time for continuing to mix and stir evenly is 1-3 min, and the time for further mixing and stirring evenly is 5-10 min.

Citation Information

Patent Citations

  • Alkali-activated slag mortar

    CN102531438A

  • Method for strengthening carbonation resistance of alkali-activated concrete

    CN109437811A

  • Additive for improving carbonization resistance of concrete as well as preparation method and application of additive

    CN113896452A

  • Method for preparing novel steel bar rust resistant agent

    CN102503237A